Al-Meseri, Abdul Wahhab. “Judaism and Postmodernism: An Epistemological View,” Year 3, Issue 10 (Fall 1418 AH/ 1997 CE), Pp. 93-122. - المسيري, عبد الوهاب (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1997)
Abdul Wahhab al-Meseri’s article offers an overview of Jewish thought and its impact on post-modern thought, which is based on the dismantling of all frames of reference and calls for diffluence and absence of centrality. His study contributes to expanding our vision of the other (the West) and differentiates between partial and comprehensive secularism. It describes how the sacred text of Judaism has been induced with heresy, and explains certain terms of post-modernism and its relationship with Jews and Judaism, such as “signifier” and “signified,” “attendance” and “absence” in Western philosophy, concentration on the logos, absolute and relative terms, and the notion of difference in place and delay in time in post-modern thought.